EXPERIMENTAL STUDIES FOR DEVELOPMENT HIGH-POWER AUDIO SPEAKER DEVICES PERFORMANCE USING PERMANENT NdFeB MAGNETS SPECIAL TECHNOLOGY - Constantin D. STĂNESCU; Liliana CAINICEANU; Simona IONESCU (Fiabilitate şi Durabilitate)
In this paper the authors shows the research made for improving high-power audio speaker devices performance using permanent NdFeB magnets special technology. Magnetic losses inside these audio devices are due to mechanical system frictions and to thermal effect of Joules eddy currents. In this regard, by special technology, were made conical surfaces at top plate and center pin. Analysing results obtained by modelling the magnetic circuit finite element method using electronic software package,was measured increase efficiency by over 10 %, from 1,136T to13T.